PROCEDURE OF ANALYSIS SERVICE DATABASE SYSTEM TIME COMPUTER NETWORK BASED ON ONLINE BANKING - Hikmayanti Hikmayanti; Hj. Latifah Dra. Hj Latifah, MM (Jurnal Sistem Informasi, 1998)
A bank serves customers primarily in deposit services require an online computer network. In this case the deposits are still using computers that stand alone, therefore, used an online computer networks and then analyze how the way the procedure database system of computer network-based deposit service online. Another obstacle that may arise such as the use of human resources who is less skilled and the technology used was not able to compete in speed and accuracy of the information produced.